2017
DOI: 10.1186/s40900-017-0067-x
|View full text |Cite
|
Sign up to set email alerts
|

Recruiting patients as partners in health research: a qualitative descriptive study

Abstract: Plain English summaryIncreasingly, funders and researchers want to partner with patients in health research, but it can be challenging for researchers to find patient partners. More than taking part in research as participants, patient partners help design, carry out and manage research projects. The goal of this study was to describe ways that patient partners have been recruited by researchers and patient engagement leads (individuals within organizations responsible for promoting and supporting patients as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(56 citation statements)
references
References 20 publications
0
53
0
2
Order By: Relevance
“…33 Moreover, stakeholders need to feel they are important members of the research team in order to sustain their engagement. 13 The need for trust and support can be achieved through face-to-face meetings, and making time to socialize with others on the team has been suggested in studies of generic stakeholders 13,[30][31][32][33] and is congruent with our second study theme, "build connections". The third enabler theme "offer financial assistance" is thought by some to be key to engagement.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…33 Moreover, stakeholders need to feel they are important members of the research team in order to sustain their engagement. 13 The need for trust and support can be achieved through face-to-face meetings, and making time to socialize with others on the team has been suggested in studies of generic stakeholders 13,[30][31][32][33] and is congruent with our second study theme, "build connections". The third enabler theme "offer financial assistance" is thought by some to be key to engagement.…”
Section: Discussionmentioning
confidence: 67%
“…For example, lack of time for engaging in research was described by many respondents as the greatest barriers to SER, a finding reported in other studies no doubt due to the universal application. [28][29][30][31][32] Culturo-linguistic tensions we defined as the lack of recognition of Indigenous "ways of knowing". In contrast, other authors referred to cultural barriers as a "power imbalance" between researchers and participants with SER sometimes viewed as acts of tokenism.…”
Section: Discussionmentioning
confidence: 99%
“…AB is working toward an electronic communication platform that allows interaction between patients and researchers and serves as a tool to recruit new council members. Ultimately, a mix of recruitment strategies is observed and necessary for the ongoing recruitment of patients (21). Members from both PACs described a wide range of involvement, spanning all stages of the health research process (Tables 1 and 2).…”
Section: Patient Advisory Council Patient Engagement Platform Albermentioning
confidence: 99%
“…[112][113][114][115][116][117] Global initiatives are ongoing to reduce barriers to patient involvement in epidemiology research, such as patient uncertainty over their role in study design and guideline development and concerns from the academic community. 116,118,119 In Australia, the Standardized Outcomes in Nephrology initiative outlined practical steps to systematically implement consumer engagement in the management and research of kidney disease and to establish a set of core outcome measures on the basis of the shared priorities of patients, caregivers, clinicians, researchers, and policymakers. 113,120 In Canada, the New Investigators in the Kidney Research Scientist Core Education and National Training Program engages patients in research to improve kidney disease outcomes and to promote the use of patient-reported outcome measures in kidney practice.…”
Section: Epidemiology Studies To Enhance the Conduct Of Clinical Trialsmentioning
confidence: 99%